Stimulating E-Business Capabilities and Digital Marketing Strategies on Business Performance in E-Commerce Industry - Del Giorgio Solfa, Federico (2023)
This study investigates how e-business capabilities and digital marketing strategies jointly influence business performance in the e-commerce industry, which has experienced unprecedented growth driven by technological advancements and changing consumer behavior. E-business capabilities encompass the use of technology and digital infrastructure, while digital marketing strategies are employed to attract and retain online customers. The study examines the effect of e-business capabilities through digital marketing strategies on the customer satisfaction and loyalty of UAE e-commerce industry. The research is descriptive and explanatory, and uses a structured 5-scale Likert questionnaire to collect data from the HR managers of 135 e-commerce companies based in UAE. The statistical analysis is performed using structural equation modeling. The findings highlight the significant relationship of the study variables. Consequently, the results of this study provide valuable insights for e-commerce businesses, elucidating the need to invest in robust e-business capabilities to support effective digital marketing efforts. Additionally, the research underscores the significance of tailoring digital marketing strategies to align with specific business objectives and customer segments. The study also contributes to the literature on digital transformation, by demonstrating how e-business capabilities and digital marketing strategies can enable e-commerce firms to adapt and thrive in the dynamic and competitive digital environment.